Organizational aspects of neurorehabilitation at the outpatient stage - Khramtsov, D.; Vorokhta, Yu.; Vikarenko, M.; Busel, S.; Sazonov, B. (Journal of Education, Health and Sport, 2021)
The study was aimed to evaluate the effectiveness of IRP implementation in patients of a specialized clinic providing long-term care to neurological and neurosurgical patients. Material and methods. The study was conducted in 2020-2021. on the basis of the MC "Expert Health" (Odessa, Ukraine). 83 patients undergoing neurorehabilitation program were examined. The correspondence of the fulfillment of key rehabilitation tasks in terms of time and quality was assessed. Additionally, the level of motivation and compliance of the patient was assessed using the MOT-Q questionnaires (for patients with previous TBI (n = 13), SRMS (for patients with stroke (n = 54) and with SRQ-E (for patients with other types of neurological pathology (n = 16). The overall level of compliance was assessed using the General Rehabilitation Adherence Scale (GRAS). The level of safety was assessed according to the following criteria: the presence of FAST certificates for personnel, a system for monitoring vital functions, equipment and consumables for the provision of emergency care. Statistical processing was carried out by methods of variance and correlation analysis, using the MedCalc 1.3 software. Results. There were not recorded any significant violations of safety principles in the provision of rehabilitation assistance in the certification of personnel according to FAST. The frequency of detecting cases of improper implementation of IRP did not exceed 6.0% (5 cases out of 83 analyzed). When assessing the relationship between the effectiveness of IRP and the level of compliance, a strong positive correlation was found - r = 0.78 Conclusion. 1. Provision of rehab services for neurological patients in the long term requires coordination of the actions of specialists at the intra-, inter-, and transdisciplinary levels. 2. A necessary condition for the functioning of a multidisciplinary team in the provision of rehabilitation care is certification of staff in the BLS systems - for allied health specialists and ACLS for physicians. 3. The effectiveness of IRP depends on the patient's compliance level (r = 0.78). 4. For the continuity of the rehabilitation process, it is necessary to involve relatives and facilitate their training in the basics of "home" rehabilitation.